Organic emitters with near-unity photoluminescence to reinforce buried interface of perovskite solar cells and modules - Suo, Zhen-Yang; Xiao, Guo-Bin; Su, Zhenhuang; Dong, Runmin; Mu, Xijiao; Gao, Xingyu; Wu, Yiying; Cao, Jing (Energy & environmental science, 2024)
Stabilizing the embedded perovskite-substrate interface without UV-vis damage remains a longstanding challenge in perovskite solar cells and modules since it leads to energy loss and phase instability under UV-vis illumination. In this work, we developed a buried interface reinforcement strategy utilizing cyano-based organic emitters with near-unity photoluminescence. Due to the dipole homogenization effect, the electron distribution around the cyano group in triphenylamine-based emitter becomes more dispersed, making it better suited to compensate for iodide vacancies and reinforce the PbI 6 octahedral configuration at the buried interface. This emitter with near-unity photoluminescence further suppresses the photochemical degradation during long-term illumination, thereby contributing to better cell performance and stability. Devices with an active area of 0.10 cm 2 obtain a champion efficiency of up to 25.67% (certified 25.09%), while the recorded efficiencies of solar modules reach 23.41% (certified 22.83%) and 21.91% for the aperture areas of 11.44 and 72.00 cm 2 . An unencapsulated device retains 90% of its original performance after 1000 h of continuous 1-sun illumination at maximum power point operating conditions. We developed an embedded perovskite-bottom interface reinforcement strategy employing cyano-based emitters with near-unity photoluminescence efficiency, to enhance the device performance and stability.